Order-theoretical connectivity - T. A. Richmond; R. Vainio (International Journal of Mathematics and Mathematical Sciences)
Order-theoretically connected posets are introduced and applied to create the notion of T-connectivity in ordered topological spaces. As special cases T-connectivity contains classical connectivity, order-connectivity, and link-connectivity.